2006
DOI: 10.1079/bjn20051643
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the antiplatelet effect of C-phycocyanin

Abstract: C-phycocyanin (cpc), a biliprotein isolated from Spirulina platensis, has been reported to exert many therapeutic and nutritional values. In the present study, we examined whether cpc has an antiplatelet activity in vitro and further investigated the possible anti-aggregatory mechanisms involved. Our results showed that preincubation of cpc (1 -50 mg/ml) with rabbit washed platelets dose-dependently inhibited the platelet aggregation induced by collagen (10 mg/ml) or arachidonic acid (100 mM), with an IC 50 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…C-phycocyanin (C-PC), a biliprotein found in blue green algae such as Spirulina platensis, is often used as a dietary nutritional supplement in many countries due to its therapeutic value, including hepatoprotective, anti-aggregatory, neuroprotective and reactive oxygen species (ROS)-scavenging actions (Kay, 1997;Romay et al, 2003;Vadiraja et al, 1998;Bhat and Madyastha, 2000;Chiu et al, 2006). In addition, the anti-inflammatory activity of C-PC has been demonstrated in various in vitro studies and in vivo experimental models such as mice with arthritis or sepsis (Romay et al, 1998;Remirez et al, 1999;Romay et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…C-phycocyanin (C-PC), a biliprotein found in blue green algae such as Spirulina platensis, is often used as a dietary nutritional supplement in many countries due to its therapeutic value, including hepatoprotective, anti-aggregatory, neuroprotective and reactive oxygen species (ROS)-scavenging actions (Kay, 1997;Romay et al, 2003;Vadiraja et al, 1998;Bhat and Madyastha, 2000;Chiu et al, 2006). In addition, the anti-inflammatory activity of C-PC has been demonstrated in various in vitro studies and in vivo experimental models such as mice with arthritis or sepsis (Romay et al, 1998;Remirez et al, 1999;Romay et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…(13,2327) In addition, the anti-inflammatory activity of PC has been demonstrated in various in vitro studies and in vivo experimental models such as mice with arthritis or sepsis. (2830) …”
Section: Introductionmentioning
confidence: 99%
“…This phycobiliprotein also induces HeLa cell apoptosis [5,6] enhances wound healing [7], retards platelet aggregation [8,9] and acts as a photodynamic agent to eradicate cancer cells in vitro [10,11]. Moreover, animal studies revealed that Cpc possesses protective effects on tetrachloride-induced hepatocyte damage [12] and oxalate-resulted nephronal impartment [13], and oral administration of Cpc successfully relieves the pathogenicity of activated brain microglia in neurodegenerative disorders [14] and exhibits a preventative effect on viral infection [15].…”
Section: Introductionmentioning
confidence: 99%